HUMAN TRAFFICKING: PROBLEMS, SOLUTIONS, AND LITERATURE REVIEW - Khudayberganov , Mavlonbek (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Human trafficking remains one of the most critical global human rights issues of the 21st century. It involves the illegal trade and exploitation of individuals through force, fraud, or coercion for purposes such as sexual exploitation, forced labor, and organ trade. According to the United Nations Office on Drugs and Crime (UNODC), millions of people, especially women and children, fall victim to trafficking networks each year. This paper explores the causes, consequences, and potential solutions to human trafficking while analyzing contemporary literature on the topic.